Intensitas Penggunaan Gadget Dan Perkembangan Kognitif Anak Usia Dini - Soni Hersoni; Anih Kurnia; Eli Kurniasih; Chita Widia (Jurnal Keperawatan Galuh, 2026)
Technological advances alter children's play patterns, making gadgets a common phenomenon. Excessive screen time in early childhood risks triggering behavioural issues and hindering overall development. This study aims to determine the relationship between gadget use intensity and early childhood cognitive development at TK Al-Ikhlas Singaparna. The research method employed a quantitative approach with a correlational design using a total sampling technique of 26 children aged four to six years. Data collection techniques included questionnaires, observation, and documentation. The results showed that respondents' gadget use intensity was high, with 12 children (46.2%) using them for more than 60 minutes per day and 57.7% predominantly using them for gaming. Inferential statistical analysis using Spearman Rank revealed a significant negative relationship with a moderate correlation strength between gadget use intensity and children's cognitive development, as evidenced by a p-value of 0.012 (p<0.05) and a correlation coefficient (r_s) of -0.485. In conclusion, higher daily gadget use intensity for passive activities like gaming is correlated with lower cognitive development attainment in preschool children. Parents are advised to implement digital parenting through strict supervision and screen time limitation to ensure children's cognitive circuits grow optimally.